Residual stress, thermomechanics & infrared imaging, hybrid techniques and inverse problems. Proceedings of the 2017 Annual Conference on Experimental and Applied Mechanics /: Proceedings of the 2017 Annual Conference on Experimental and Applied Mechanics. Volume 8 : ([2018]) - Unknown
No abstract available